Challenges in contemporary mixed media collections : storage and preventative conservation of South African artists’ books at the Jack Ginsberg Centre for book arts - Loubser, Maggi (University of Pretoria, 2023)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2022.